Rancang Bangun Alat Pengupas Talas guna Mempermudah dan Mempercepat Proses dengan Metode Quality Function Deployment - Permana, Vito Aditya; Murnawan, Hery (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Taro Chips MSMEs Mr. Ferdianto in Kesimantengah Village, Mojokerto, produces taro chips with a daily capacity of 60 kg. The process of stripping taro was previously carried out manually, taking up to 30 minutes for 3 kg of raw materials, thus limiting production capacity. This research aims to design a taro peeling machine that is able to process 5 kg in just 5 minutes. The test results show a significant increase in efficiency and productivity. With its ergonomic design and larger capacity, it is able to meet the increasing market demand and support sustainable business growth. Keywords: MSME, Productive Capacity, Production Efficiency, Productivity, Taro Peeling Machine.